2007
DOI: 10.1128/jcm.01477-07
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable DNase Is Superior to Tube Coagulase for Direct Detection of Staphylococcus aureus in Positive Blood Cultures

Abstract: ᰔIn a recent edition of the Journal of Clinical Microbiology, Qian et al. described the sensitivity and specificity of the direct tube coagulase (DTC) test for the presumptive identification of Staphylococcus aureus directly from positive blood culture bottles from which Gram stains were consistent with staphylococci (7). The reported sensitivities of 34% at 2 h of incubation and 65% at 4 h of incubation (7) are considerably lower than those previously described and suggest an unacceptably high rate of false n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
4
19
0
1
Order By: Relevance
“…As regards the DTCT, a wide range of sensitivity is reported in different times and in different papers. Our data are in range with those published in the majority of the studies (11,(19)(20)(21). It has to be noted that among the four strains which gave negative results after 24 h, in three cases the test repeated the day after provided a positive result, confirming in our experience some kind of intrinsic variability of the method.…”
Section: Resultssupporting
confidence: 90%
“…As regards the DTCT, a wide range of sensitivity is reported in different times and in different papers. Our data are in range with those published in the majority of the studies (11,(19)(20)(21). It has to be noted that among the four strains which gave negative results after 24 h, in three cases the test repeated the day after provided a positive result, confirming in our experience some kind of intrinsic variability of the method.…”
Section: Resultssupporting
confidence: 90%
“…The sensitivity of this agglutination method after a short period of subculture incubation is higher than that reported for direct testing by Staphaurex Plus on the bacterial pellet (23%) (5) and is also higher than that reported for the tube coagulase test (65 to 85%) (1,4) and comparable to the sensitivities of fluorescent in situ hybridization (98%) (1,3) and the thermostable DNase test (100%) (2). Although this technique utilized the Slidex Staph Plus test, which is considered a reliable agglutination test (6), other agglutination tests will probably have comparable results.…”
Section: Rapid Identification Of Staphyloccocus Aureus In Positive-tementioning
confidence: 57%
“…Berends et al determined that Nuc contributes to the severity of CA MRSA lung infection and evasion of neutrophil extracellular traps (8). The production of Nuc is conserved across methicillin-susceptible S. aureus and MRSA strains (9), and thus, it has been used as a marker for the direct detection of S. aureus (10). We recently demonstrated that Nuc has an additional role in S. aureus as a modulator of biofilm formation (9).…”
mentioning
confidence: 88%